EXPLOITATION OF CHILDREN AGED 5-6 YEARS OLD IN SRI AGUNG VILLAGE, KARANG AGUNG ILIR DISTRICT, BANYUASIN REGENCY - monica evi apriyanti; Febriyanti Febriyanti; Ali Murtopo (Universitas Muhammadiyah Pontianak, 2023)
The large number of young children who work on plantations in the village causes the growth and development of children to not develop properly. This attracted the attention of researchers to discuss early age exploitation in Sri Agung Village, Karang Agung Ilir District. The purpose of this study was to determine the forms of child exploitation and the supporting and inhibiting factors of early childhood exploitation in Sri Agung Village, Karang Agung Ilir District. This type of research is qualitative with a case study approach. The informants in this study consisted of 10 people (parents/community) and 5 people (early children) as well as the village head. Data collection techniques in this study used the methods of observation, interviews, and documentation. The data analysis technique used is the data reduction stage, the data presentation stage, and the conclusion drawing/verification stage. Based on the results of this study, there are several parents who invite their children to work because it is to meet their daily needs. Factors that support the occurrence of exploitation are economic factors, environmental factors, educational factors. The lack of extensive knowledge by the parents resulted in the exploitation of early childhood such as physical exploitation as well as economic exploitation. With this research, parents become more aware of how to treat their children, protect and educate children so that they are not wrong in relationships and others. So that the growth and development of children can run optimally. Keywords: Child Exploitation, Early Childhood, Supporting Factors